Selection of Proton Pump Inhibitors (PPIs) for Formulary Inclusion Using an Objective Scoring System in Malaysia - Lynette Lima, Mohamed Izham M.Ib (Journal of Applied Pharmaceutical Science)
The main aim of this study was to develop an objective Drug Evaluation Scoring System (DESS) by determining criteria for differentiation among 5 PPI drugs available in the market i.e. esomeprazole, lansoprazole, omeprazole, pantoprazole and rabeprazole. Secondly, was to assign weightage according to its importance of the criteria. Thirdly, was to determine the scores and rank the PPI drugs. In developing DESS, 200 points was assigned for the clinical documentation criterion, 300 points for the clinical efficacy criterion, 200 points for the safety criterion and 300 points for the cost criterion. The higher the assigned score, the higher importance the criterion is. The criteria were designed in the format of questionnaire to enable participants to allocate scores according to their perception on the importance of the criteria. Self-administered questionnaires were distributed to 165 specialists and medical officers. Study findings from the scoring system found that all PPI drugs have very negligible difference in clinical efficacy and clinical safety. Omeprazole was found to be the most cost economical PPI in the government hospitals. The DESS was able to compare and rank PPI drugs based on the scoring system and also assist in the selection of PPI drugs into the drug formulary.
Keywords: â Â €Â ˜Drug evaluationâ Â €Â ™,â Â €Â ˜Drug formulary,â Â €Â ˜Formulary management&acirc